Environmental Education: An Ecocritical Reading of Jean Rhys’s Wide Sargasso Sea (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Anthropocentrism places human beings at the centre of the universe and postulates nature as a simple product to be consumed for the interests of humanity. Anthropocentrism comes directly from the biblical account of the creation and the story reads that God gave absolute power to man ‘over the fish of the sea, and over the birds of the air, and over the cattle, and over all the earth’ (The Book of Genesis) Almost all Judeo-Christian Abrahamic faiths and modern western ideologies uphold this view. Throughout history, religion, and later on, industrial development adversely affected the relationship between human and non human world. Religion gave so much importance to humans that they ventured to destroy nature to have more and more power over it and industrialism estranged man from nature to such an extent that now nature and culture or civilization for all practical purposes have become altogether two different realms. Ecocentrism places ecosystem at the centre and says that nature has its own agency and is an end in itself. As opposed to the biblical myth, ecocentric belief looks at nature as a sacred space and teaches respect for all forms of life. Physical nature is holy and each living being has a special bond with the particular physical place that it inhabits and there is absolute interdependence and reciprocity. Questions related to Anthropocentrism and ecocentrism are part of a larger ecocritical debate and worldview, and literary texts that present themselves to ecocritical readings are at the center of this debate. It is the environmentally oriented literary texts that challenge the nature/culture divide and call for the resolution of the crisis. Lawrence Buell, who in the words of Richard Kerridge ‘has done more than any critic to give ecocriticism an explicit method’ has made a list of themes and subthemes that makes a literary text ‘environmentally oriented’ and these are the principles that can help a text to overcome the mad and greedy norms of the anthropocentric world.